The Arc of Crisis in the MENA Region Fragmentation, Decentralization, and Islamist Opposition - Karim Mezran (Pubblicazioni ISPI, 2018)
The Arc of Crisis in the MENA Region volume deals with the countries of the Middle East and North Africa that are facing a particularly troubled period in their historical development. Syria, Iraq, Libya, Egypt and to a lesser extent Jordan and Tunisia have plunged into a legitimacy crisis that in some cases has turned into civil war or violent upheaval. As traditional authorities lose their legitimacy, two alternatives are emerging. The first is a more decentralized system of government, evinced by the empowerment of subnational government bodies and the growing legitimacy of local authorities; in this trend, the local authorities are able to keep the state united and more functional. The second is a growing number of political groups that act as opposition to authoritarianism, which is experiencing a revival. The analysis herein also focuses on Islamist movements; namely, their organizational and ideological development as well as how the shrinking of the political space affects them and the entire polity. This Report explores the distinctive dynamics and characteristics of these challenges in the post-Arab Spring era.